Volunteering as a determining factor in resilience and mastering emotions: the case of social work students - Salvador-Ferrer, Carmen; Jurado-Pérez, María Daniela; Rodríguez-Fernández, Ascención Gumersinda (Acciones e Investigaciones Sociales, 2019)
This study aims to inform on the relationship between vo- lunteering, emotional intelligence and resilience, by looking at a sample of 47 Social Work undergraduates. Data were collected using the following scales: Volunteer Motivation, Trait Meta-Mood Scale, and Resilience Sca- le. The results show that students have a positive view of the practice of volunteering. In addition, we have also detected a relationship between the knowledge obtained from doing voluntary work, emotional regulation, and perseverance. Furthermore, a theoretical causal model for mediation is offered to explain the relationship between these variables. In particular, the data indicate that knowledge has an impact on emotional regulation and that this affects perseverance. Finally, the practical repercussions of this study underline the need to encourage the practice of voluntary work.
Keywords: volunteering/voluntary work; emotional intelligence; resilience; Social Work students